Respostas

  • Usuário do Brainly
2013-10-23T23:32:42-02:00
7x - 6x = 6 - 1
x = 5




5x - 2x = - 9 + 3
3x = - 6
x = -6/3
x = -2


5x - 10 = 4 + 2x - 1
5x - 2x = 3 + 10
3x = 13
x = 13/3


46 + 3x = 6x - 8 + 26
3x - 6x = 18 - 46
- 3x = - 28 .(-1)
3x = 28
x = 28/3



3x - 9 = x + 3
3x - x = 3 + 9
2x = 12
x = 12/2
x = 6


6x - 3 = 2x + 5
6x - 2x = 5 + 3
4x = 8
x = 8/4
x = 2




6 + 2y = 26
2y = 26 - 6
2y = 20
y = 20/2
y = 10

2 4 2
2013-10-24T08:56:50-02:00
7x+1=6x+6=
7x-6x=6-1
x=5

 5x-3=2x-9
5x-2x=-9+3
3x=12
x=4

5.(x-2)=4+2x-1
5x-10 =4+2x-1
5x-2x=10+4-1
3x=13
x=13/3

50+3x-4=2.(3x-4)+26
50+3x -4= 6x-8 +26
3x-6x=-50+4 -8+26
-3x=72  multiplica por -1 para o x ficar positivo
x=-72/3
x=-24

2x+1x-9=x+3
2x + x -x= 3+9
2x =12
x=12/2
x=6

6x-3=2x+2+3
6x-2x=2+3+3
4x= 8
x=8/4
x=2

6+2y=16+10
2y=16+10-6
2y=20
y= 20/2
y=10
1 5 1